HUBUNGAN KECERDASAN EMOSIONAL, KETERAMPILAN KEPEMIMPINAN SITUASIONAL DAN KINERJA PENGELOLA FAKULTAS: STUDI PADA EKONOMI DAN MANAJEMEN UNIVERSITAS SAMAWA SUMBAWA BESAR - S Sulistianingsih; S Syafruddin (Jurnal Ekonomi & Bisnis, 2022)
This research was conducted with the aim of knowing the effect of Emotional Intelligence and analyzing the Effect of Situational Leadership Skills on the Performance of Managers of the Faculty of Economics and Management, Samawa University. The type of research used is descriptive. The type of data in this study is quantitative with primary data used in the form of direct information obtained from questionnaires filled out by respondents from lecturers, TU staff and students of the Faculty of Economics and Management, Samawa University batch 21 and batch 22. The analytical tools used in this study is Software Smart PLS 3.0 M3. The results showed that emotional intelligence had no significant effect on the performance of the managers of the Faculty of Economics and Management, Samawa University, while situational leadership skills had a positive and significant effect on the performance of the managers of the Faculty of Economics and Management, Samawa University.